Climate Change and Economic Growth in Lebanon - Taher, Hanadi (International Journal of Energy Economics and Policy, 2019)
This paper examined the relation between the climate change and economic growth in Lebanon. Time series analysis for the period 1990-2013 based on ordinary least squares (OLS) estimation technique were used. Changes in annual rainfall, carbon dioxide emission, temperature changes, and forest areas were used to capture climate change, while gross fixed capital formation, labor force and urbanization were used as control variables. The results indicate that two climate variables have negative impact (carbon dioxide emissions and forest areas) and two positive impact on the Lebanese economic growth (rainfalls and temperature changes). However, only rainfalls variable is statistically significant. All the control variables were statistically significant have the theoretical expected signs. These results imply that Lebanese policy makers should implement strategies to minimize the effect of carbon dioxide emissions and forest depletion. Based on this, a specialized national council should be initiated to put series studies to deal with all climate change issues. After testing the stationarity levels, the co-integration tests confirm the existence of co-integrating relationship between the variables. Keywords: Climate Change, Economic Growth, Ordinary Least Squares, co-integration tests. JEL Classifications: Q20, Q43, Q54, O44 DOI: https://doi.org/10.32479/ijeep.7806